2007
DOI: 10.1152/ajprenal.00300.2006
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of osmotically inactive Na+ by growth and by dietary salt restriction in rats

Abstract: The idea that an osmotically inactive Na(+) storage pool exists that can be varied to accommodate states of Na(+) retention and/or Na(+) loss is controversial. We speculated that considerable amounts of osmotically inactive Na(+) are lost with growth and that additional dietary salt excess or salt deficit alters the polyanionic character of extracellular glycosaminoglycans in osmotically inactive Na(+) reservoirs. Six-week-old Sprague-Dawley rats were fed low-salt (0.1%; LS) or high-salt (8%; HS) diets for 1 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 22 publications
4
84
2
2
Order By: Relevance
“…Along with others (4-7), we (8)(9)(10)(11)(12)(13)(14) showed earlier that electrolytes are distributed in a more complex 3-compartment model, in which intravascular and the interstitial fluids do not equilibrate as readily as believed (15,16). We underscored the importance of Na + binding to negatively charged proteoglycans in the skin, the largest organ with the most extracellular space (8,11). We suggested that, in addition to renal control, local extrarenal regulatory mechanisms for electrolyte clearance of interstitial fluid are operative to maintain extracellular electrolyte clearance and blood pressure.…”
Section: Introductionmentioning
confidence: 54%
“…Along with others (4-7), we (8)(9)(10)(11)(12)(13)(14) showed earlier that electrolytes are distributed in a more complex 3-compartment model, in which intravascular and the interstitial fluids do not equilibrate as readily as believed (15,16). We underscored the importance of Na + binding to negatively charged proteoglycans in the skin, the largest organ with the most extracellular space (8,11). We suggested that, in addition to renal control, local extrarenal regulatory mechanisms for electrolyte clearance of interstitial fluid are operative to maintain extracellular electrolyte clearance and blood pressure.…”
Section: Introductionmentioning
confidence: 54%
“…They first showed that Na ϩ retention during high salt feeding was associated with increasing GAG content in cartilage and skin (468). Then, they measured osmotically active and inactive Na ϩ (i.e., Na ϩ accumulation without corresponding accumulation of water) during growth of rats on a low-(0.1%) vs. high-salt (8%) diet (412) and found that while salt was lost from the body during growth, there was additionally a dietary-induced salt loss of osmotically inactive Na ϩ that originated mostly from skin. Long-term salt deprivation resulted in a shift of PG composition with reduced sulfated PGs and increased hyaluronan, which lowered the charge density and water-free Na ϩ binding to the ECM.…”
Section: B Charge Of the Interstitiummentioning
confidence: 99%
“…Chemical analysis of the carcasses included Na ϩ , K ϩ , Cl Ϫ , and water measurements after dry ashing of the different tissues as reported previously. 8,10 We calculated the Cl Ϫ space as a measure of the extracellular volume from the tissue Cl Ϫ content and the serum Cl Ϫ concentration. The Cl Ϫ -free water space was calculated as a measure of the intracellular volume.…”
Section: Animal Experimentsmentioning
confidence: 99%